A bibliometric analysis of diabetic gastroparesis from 1979 to 2024 - Xu, Hui; Miao, Furui; Fan, Yushan (Frontiers in Medicine, 2024)
Objective Gastroparesis is one of the complications of diabetes mellitus, which has a major impact on the quality of life of patients, and the limited therapeutic options currently available make it a public health problem. No bibliometric studies on diabetic gastroparesis have been published to date. Therefore, the aim of this paper is to summarize and analyze the research hotspots for researchers. Methods Research articles related to Diabetic gastroparesis were searched in Web of Science Core Collection (WOSCC), and relevant information was extracted after screening. A comprehensive bibliometric analysis of 699 publications was conducted using Microsoft Excel 2019, Citespace and VOSviewers. Result A total of 699 papers from 738 institutions in 41 countries were retrieved. Publications in this field have increased rapidly since 1979. USA (n = 370) and Mayo Clinical (n = 69) were the most productive country and institution, respectively. Neurogastroenterology and Motility (n = 67) was the most published journal with Parkman, Henry P. (n = 40) having the highest number of articles; Gastroenterology and Mccallum, Richard W. were the most influential journals and authors. Conclusions The research hotspots of Diabetic gastroparesis are mainly focused on treatment modalities and pathological mechanisms. Future research in diabetic gastroparesis will focus on exploring the pathomechanisms, finding long-term effective treatments, and improving patients' quality of life.